Analysis of Infants Based on Data from the German Perinatal Survey of the Years 1994–2011 in Mecklenburg-Pomerania, Germany. Classification of Infants with regard to their Gestation Duration and Birth Weight - Schneider, D.; Radloff, S.; Müller, S.; Möller, D.; Bolz, M.; Briese, V. (Zeitschrift für Geburtshilfe und Neonatologie, 2015)
Background:  The demographic change in Germany describes an ongoing process of population development of which the eastern German states tend to be more affected. These ongoing changes have an influence on the reproductive behavior of the population. After twenty-three years of German reunification, the present study has investigated the question to what extent the somatic classification of newborns in Mecklenburg-Pomerania (M-P), Germany, is affected.Material and Methods:  Newborn singleton births (n=174 084) were classified from the existing data of the German Perinatal Survey between 1994 and 2011. The rate of premature birth, SGA, and LGA rate as well as the rate of low birth weight ≤2 499 g were determined both genderdependently and independently. In addition, a combined analysis of the rates has been taken into account. The obtained data material from M-P made it possible for the first time to compare by values. National and international reference studies were considered in this comparison.Results:  In M-P, the premature birth rate is 5.2%; the rate of newborns with low birth weight ≤ 2 499 g is 4.4%. Among newborns of ≤2 499 g and SGA newborns, girls compose a higher percentage (4.7%, 12.5%) compared to boys (4.0%, 7.4%). The premature birth rate and LGA newborns appear conversely. For these, the percentage of boys (5.6%, 12.6%) is higher than that of girls (4.8%, 7.0%). 60.6% of the gender non-specific newborns ≤2 499 g are simultaneously premature newborn infants. Only a very small percentage of 0.5% of SGA newborns is at the same time premature infants and newborns with low birth weight.Conclusions:  By getting nationwide country-specific figures, a detailed analysis of the newborns in M-P can be performed. The analysis supports the existing national values and is a helpful addition for practice-oriented advice.
Keywords: somatic classification of newborns; premature birth; low birth weight; SGA neonates; Mecklenburg-Pomerania; Germany